2009
DOI: 10.1016/j.jacc.2008.11.056
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-Dependent Regulation of the Mechanical Properties of Aortic Valve Cusps

Abstract: These data highlight the role of the endothelium in regulating the mechanical properties of aortic valve cusps and underline the importance of valve cellular integrity for optimal valve function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 14 publications
1
87
0
Order By: Relevance
“…Additionally, the presence of α-SMA-positive stress fibers (Fig. 3A) (37,38) that respond to vasoactive mediators such as endothelin-1 (ET-1) and serotonin (4,5). We asked if we could measure the extent of EMT via a functional transformation of the normally noncontractile VEC to a contractile VIC.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the presence of α-SMA-positive stress fibers (Fig. 3A) (37,38) that respond to vasoactive mediators such as endothelin-1 (ET-1) and serotonin (4,5). We asked if we could measure the extent of EMT via a functional transformation of the normally noncontractile VEC to a contractile VIC.…”
Section: Resultsmentioning
confidence: 99%
“…This reduction indicates that eNOS might be involved in the fibrosa susceptibility in CAVD pathogenesis . Moreover, inhibition of eNOS expression results in increased cusp stiffness of the aortic valve (El-Hamamsy et al, 2009). Statins decreased the amount of calcification and increased VEC eNOS in rabbits, which suggests that eNOS may protect against CAVD.…”
Section: Endothelial Dysfunctionmentioning
confidence: 95%
“…Studies have demonstrated that VECs interact with VICs in a complex hemodynamic and mechanical environment to maintain aortic valve cusp tissue integrity. Additionally, VECs regulate VIC function through paracrine signals, such as controlling VIC contractility and leaflet mechanics (El-Hamamsy et al, 2009). More specifically, valvular endothelial dysfunction has been implicated as the initiator of inflammatory reactions, blood clots, and even calcification .…”
Section: Cellular Interactionmentioning
confidence: 99%
“…It was reasoned that the pulmonary autograft, although subjected to systemic pressure would, as a living valve, be able to adapt. as it turns out, the aortic valve has several sophisticated features that are dependent on its viability [4][5][6] . The different parts of the aortic valve change their size and shape during the cardiac cycle.…”
Section: Rationalementioning
confidence: 99%
“…This property can affect left ventricular workload and possibly coronary flow, together with stress distribution on the valve leaflets. Furthermore, living aortic valve leaflets modify their stiffness in response to humoral and endothelial-derived signals, allowing them to adapt to changes in haemodynamic conditions 5 .…”
Section: Rationalementioning
confidence: 99%